Characteristics of indoor/outdoor PM2.5 and related carbonaceous species in a typical severely cold city in China during heating season. (1st February 2018) - Xiao, Ye; Wang, Lina; Yu, Mingzhou; Shui, Taotao; Liu, Lin; Liu, Jing
Abstract: The particle pollution has been getting worse for several decades in China, it is necessary to investigate the characteristics of particles in the living environment. Fine particulate matter (PM2.5 ) in air particles attracted wide attention because of its series harm to human health. In this study, a measurement campaign of sampling indoor and outdoor PM2.5 was carried out in a residential quarter in Harbin from October 2015 to March 2016, to investigate the connection between indoor and outdoor fine particles. The study included two indoor sites (Indoor-1 and Indoor-2), an outdoor site (Outdoor), and a site near the regional heat source for the entire residential quarter (Heating Source). The characteristics of PM2.5, organic carbon (OC), and element carbon (EC) were studied in the indoor and outdoor environment. Results showed average PM2.5 mass concentrations for heating source site, outdoor site, and two indoor sites were 105.11, 87.39, 61.71 and 58.48 μg/m 3 respectively. As for carbonaceous species, the average concentrations for each site were 25.97, 23.50, 20.31 and 19.03 μg/m 3 for OC, and 6.44, 5.82, 3.98 and 3.81 μg/m 3 for EC respectively. A strong connection between indoor and outdoor PM2.5 and carbonaceous species in PM2.5 was also found, based on analyses of indoor to outdoor (I/O) ratios and linear regression equation for indoor/outdoor PM2.5, OC, and EC. Furthermore, results indicated that activities such as cooking and cleaning affected indoor PM2.5 concentrations to a certain degree. Strong correlations were found between OC and EC at all four sampling sites. Graphical abstract: Highlights: Sampling occurred at two indoor sites, one outdoor and one heating source site. Trends of PM2.5, OC and EC mass concentrations over time were generally consistent. Strong correlations between OC and EC at four sampling sites are observed. Average I/O ratios were generally less than 1.0 for PM2.5, OC and EC. Correlations of indoor/outdoor mass concentrations for PM2.5, OC and EC are strong.